INOVASI PEMBELAJARAN PAI DENGAN PENGEMBANGAN MODEL CONSTRUCTIVISM PADA JENJANG PENDIDIKAN DASAR DAN MENENGAH - Fitri Oviyanti (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
So far, the methods used by teachers in the learning process tend to conventional teaching methods which only includes students come , sit , write material that has been written by the teacher on the board , listening to the teacher explaining the material and do the work , using the lecture method . The impact, learning tends to be passive and bored quickly. This kind of learning situation is almost no opportunity for students to express their creativity, so the quality of the quality of learning also becomes low. Constructivism learning model seems to be one of the answers to these problems. Therefore, in this learning model students are preferred. Teaching and learning process in constructivism model student centered more colored than teacher centered. Constructivism model is more empowering for the class as a learning centered not for teaching; not teaching process but learning process. This is in accordance with the curriculum 2013, is autenthic assessment; assessment process and results.